Enterobacterias productoras de B-lactamasas de espectro extendido aisladas de hemocultivos en un Hospital Universitario de Venezuela - Sandrea-Toledo Lisette; Paz-Montes América; Piña-Reyes Eyilde; Perozo-Mena Armindo (Kasmera, 2007)
Abstract: The extended-spectrum -Lactamase (ESBL) is an important mechanism of resistance to the antimicrobial agents in members of the Enterobacteriaceae family. The objective of the present study was to determine the frequency of extended-spectrum betalactamase-producing enterobacteria isolated from hemocultures at a University Hospital. 21.023 hemocultures from the Bacteriological Reference Center of the Autonomous Service at the University Hospital, Maracaibo, Venezuela were processed during the period of June 2002 to June 2006. They were studied according to the conventional technique described by Murray (2003), and the enterobacteria were identified using the methodology of Edward and Ewing (1996). For susceptibility tests, methodology suggested by Bauer y Kirby (1996), according to CLSI norms (2006) was followed, and for ESLB production, methodology suggested by Jarlier (1988) was used. Of the total hemocultures processed, 2.371 (11.8%) resulted positive, and in 384 (16.20%), enterobacteria were isolated and 152 strains (39.48%) turned out ESLB+. Klebsiella pneumoniae was the predominant specie and of 158 strains, 97 (61.39%) were ESLB+, followed by Escherichia coli with 122 isolates, 37 (30.33%) of them ESLB+. Other ESLB-producing species found were: Morganella morgannii (1/4: 25.0%), Enterobacter cloacae (11/45: 24.44%), Serratia marcescens (2/9: 22.22%), Klebsiella oxytoca (3/14: 21.43%), and Enterobacter aerogenes (1/5: 20.0%). A high resistance to aminoglycosides and a low resistance to quinolines were observed in the ESLB-producing enterobacteria studied. ESLB production in enterobacteria has become a therapeutic problem worldwide, mainly if they are producing bacteremia.